The Lithuanian Have-Resultative – A Typological Curiosum? - Wiemer, Björn (Lingua Posnaniensis, 2013)
This article presents the Lithuanian possessive resultative construction with the verb turėti ‘have’ and discusses its place in a typology of forms of resultative constructions. While possessive resultatives with a past passive participle (as in Polish Kolację mamy już przygotowaną lit. ‘We have the dinner already prepared’) are found in areally related as well as other languages, Lithuanian stands out in using an active participle (more precisely: a participle always oriented toward the highest-ranking argument). The construction can be regarded as a rarum. However, it most probably did not develop in the way proposed by HARRIS (2010) as explanation for the emergence of rara. The rarity of the Lithuanian construction calls for an in-depth diachronic study, whose results may shed new light on the development of rare linguistic features.